PERANCANGAN APLIKASI RESERVASI FUTSAL (FUTSAL-IN) GUNA MEMPERMUDAH PEMESANAN APLIKASI SECARA ONLINE : DESIGNING A FUTSAL RESERVATION APPLICATION (FUTSAL-IN) TO FACILITATE ONLINE BOOKING APPLICATIONS - M. Gilang Ramadhan; Muhammad Arafah Alif; Muhammad Imran Hidajat H; Putri Nirmala; Nurrahmah Agusnaya; Wahyu Hidayat M (CV. Sakura Digital Nusantara, 2025)
The futsal reservation application is an innovative solution to facilitate the online field booking process. This article discusses the design of the Futsal-In application, which aims to simplify and enhance user experience in booking futsal fields efficiently. The design methods used include user needs analysis, user interface (UI) design, and development of a platform-based digital application. The Futsal-In application allows users to easily select the field, time, and desired duration, as well as make online payments. Through this approach, it is hoped that the Futsal-In application can improve efficiency in the futsal field booking process and enhance user satisfaction.